Reproductive Health Model Curriculum, 2nd Edition (Out of Print) - Jennifer Hurlburt (Association of American Medical Colleges, 2006)
Abstract This seven-module reproductive health model curriculum is a comprehensive resource designed to help fill education and training gaps in reproductive health medical education. The curriculum addresses typical areas of reproductive health, such as sexually transmitted diseases and contraception, but also covers one of the most essential aspects of quality health care, effective communication for health care providers. The curriculum also includes learning objectives from the Association of Professors of Gynecology and Obstetrics Women's Health Care Competencies for Medical Students. Since its release, this curriculum has been incorporated into electives and clerkships in at least 24 US medical schools, accessed by students and/or faculty at 72 US medical schools, and disseminated in at least 24 countries worldwide. It has been updated to address advances in the field of reproductive health, expand access to educational resources, and increase the utility of the resource. Users are encouraged to adapt its content to fit their specific curricular needs.